2011
DOI: 10.1016/j.aap.2010.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for fatal crashes in rural Australia

Abstract: This paper presents findings from the rural and remote road safety study, conducted in Queensland, Australia, from March 2004 till June 2007, and compares fatal crashes and non-fatal but serious crashes in respect of their environmental, vehicle and operator factors. During the study period there were 613 non-fatal crashes resulting in 684 hospitalised casualties and 119 fatal crashes resulting in 130 fatalities. Additional information from police sources was available on 103 fatal and 309 non-fatal serious cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 13 publications
2
37
0
1
Order By: Relevance
“…Similar results were found in other studies. In Queensland between 2004and 2007, Siskind et al (2011 found that 75 percent of fatally injured drivers in traffic accidents were male, and their median age was 34. Turner and McClure (2003) conducted a study with 685 male and female victims aged 17 to 88 years.…”
Section: Victims Who Were Driversmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were found in other studies. In Queensland between 2004and 2007, Siskind et al (2011 found that 75 percent of fatally injured drivers in traffic accidents were male, and their median age was 34. Turner and McClure (2003) conducted a study with 685 male and female victims aged 17 to 88 years.…”
Section: Victims Who Were Driversmentioning
confidence: 99%
“…The time delay between identifying an event and executing an operation is longer (Sutlovic et al 2011). Numerous studies have shown that drinking is a major factor for mortality in road traffic accidents (Clarke et al 2010;de Carvalho et al 2011;Siskind et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The number of crashes and severity of injury by distance driven are highest in young drivers (15-25 yr) and in those over the age of 65 years (2,3). Fatality reduction currently targets increasing seat belt use and reducing speeding and alcohol (4,5). However, inattentiveness, fatigue, and sleepiness are increasingly recognized as contributing, and possibly primary, factors (4, 6).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also investigated the factors affecting the involvement in a fatal crash as a function of individual characteristics. The important individual behavioral determinants of fatal crashes include excessive speed, violation of traffic rules and lack of seat belt use (Siskind et al, 2011;Valent et al, 2002;Sivak et al, 2010;Viano and Parenteau, 2010). Other driver attributes such as aggressive driving behavior, unlicensed driving and distraction during driving are identified to be the most significant contributors of fatal crashes for young drivers (Lambert-Bélanger et al, 2012;Hanna et al, 2012;Chen et al, 2000).…”
Section: Introductionmentioning
confidence: 98%